Types and Forms of Independent Work of Students In English Lessons (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
It is necessary to note the importance of a scientifically based classification of independent work, since without focusing on it it is impossible to build an effective system of independent work for students. It must be said that today there are various classifications of independent work. Some researchers classify them according to goals, others - according to the nature of the educational tasks performed by students during independent work, others take the nature of educational activity in the process of solving various problems as the basis for the classification, and in the works of others, attempts have been made to create a classification of independent work that would take into account the most generalized grounds.